Explodability criteria for the neutrino-driven supernova mechanism - Maltsev, Kiril; Schneider, Fabian; Mandel, I.; Müller, B.; Heger, Alexander; Röpke, Friedrich; Laplace, Eva (Arxiv, 2025)
Massive stars undergoing iron core collapse at the end of their evolution terminate their lives either in successful or failed supernovae (SNe). The physics of core collapse supernovae (CCSNe) is complex, and their understanding requires computationally expensive simulations. The sampling of large, densely sampled parameter spaces of SN progenitors, as is needed e.g. for population synthesis studies, is thus not feasible. To remedy this situation, we present criteria that allow us to predict the final fates of stars by evaluating multiple explodability proxies derived from the stellar structure at the onset of core collapse. These are formulated based on the outcomes of a semi-analytic supernova model, evaluated over a set of ~3,900 heterogeneous stellar progenitors (single stars, binary-stripped and accretor stars). Over these, the explodabiliy criteria achieve an accuracy of >99% agreement with the semi-analytic model. The criteria are tested on 29 state-of-the-art 3D CCSN simulation outcomes from two different groups. Furthermore, we find that all explodability proxies needed for our pre-SN criteria have two distinct peaks and intervening valleys as a function of the carbon-oxygen (CO) core mass $M_CO$, which coincide with failed and successful SNe, respectively. The CO core masses of explodability peaks shift systematically with metallicity, $Z$, and with the timing of hydrogen-rich envelope removal in binary-stripped stars. With these, we identify critical values in $M_CO$ that define windows over which black holes form by direct collapse. The outcome is a CCSN recipe based on $M_CO$ and $Z$, applicable for rapid binary population synthesis and other studies. Our explodability formalism is consistent with SN observations that constrain the progenitor $M_CO$ and partially addresses the missing red supergiant problem by direct black hole formation.